CT-Guided Pelvic Lymph Nodal Brachytherapy - Kunogi, Hiroaki; Hsu, I-Chow; Yamaguchi, Nanae; Kusunoki, Soshi; Nakagawa, Keiko; Sugimori, Yayoi; Fujino, Kazunari; Terao, Yasuhisa; Ogishima, Daiki; Yoshimura, Ryoichi; Sasai, Keisuke (Frontiers in Oncology, 2021)
Purpose: This is a report of our initial experience using computed tomography (CT)-guided interstitial high dose rate (HDR) brachytherapy to treat bulky pelvic nodal metastases as a part of definitive radiotherapy. Material and methods: Between February 2015 and April 2019, 14 cervical/endometrial cancer patients presenting with bulky pelvic node(s) underwent nodal interstitial brachytherapy boost in our institution. In total, 17 nodes were treated. The median maximum diameters of the positive nodes at the time of diagnosis and at the first nodal implant were 25 mm (range: 10–65 mm) and 16 mm (range: 9–51 mm), respectively. Dosimetry data of the lymph nodal target volume and small bowel were collected and compared using the paired-sample t-test. Treatment-related toxicities were classified using the Common Terminology Criteria for Adverse Events version 4.0. Results: The median follow-up time for all patients was 26 months. Local recurrence in pelvic nodes occurred in one patient (7%) after 16 months. One patient experienced grade 3 bladder bleeding, and one patient experienced grade 2 pubic bone fracture. No patient had grade 2 or greater gastrointestinal toxicity. In the dosimetric analysis, the mean nodal brachytherapy D90% in terms of the total equivalent dose of 2 Gy (EQD2) was 65.6 Gyαβ10. The mean small bowel dose (SBD)0.1cc and SBD1cc in terms of the total EQD2 were 60.4 and 56.5 Gyαβ3, respectively. Nodal D90% was significantly higher in terms of the total EQD2 than the SBD0.1cc (p = 0.003) and SBD1cc (p < 0.001). The Kaplan-Meier 2-year pelvic control estimate was 90%. Conclusions: CT-guided interstitial HDR pelvic nodal brachytherapy appears to be well tolerated with excellent local control in cervical or endometrial cancer patients with bulky pelvic nodes. This approach may offer a useful therapeutic option for unresected bulky pelvic nodes.